Usia, Kebersyukuran, dan Subjective Well-Being pada Guru Taman Kanak-Kanak - Wahidah, Fatin Rohmah Nur; Oktaviana, Fannisa Dwi; Sulthani, Rifki Hanif; Permadi, Iman (UIN Sunan Kalijaga, 2024)
Kindergarten teachers subjective well-being is considered essential for teaching and learning success. This study aims to determine the effect of gratitude on the subjective well-being of kindergarten teachers, which is moderated by age. The quantitative approach is used in this study, with the number of respondents 72 Aisyiyah Kindergarten teachers in Purwokerto. The instruments used are the subjective well-being scale modified from the SWLS and SPANE scales by Diener et al. (2009) with Cronbach’s ⍺ = 0,839 (15 items), the gratitude scale modified from the GRAT scale by Watkins, Woodward, Stone, and Kolts (2003) with Cronbach’s ⍺ = 0,901 (32 items), and also age demographic data. Multiple regression analysis is used to determine the effect of the variables and their moderating effect, assisted by the Jamovi 1.8.4 software. The results of the study show that there is a significant effect of gratitude on the subjective well-being of kindergarten teachers. Age is also statistically and significantly proven to moderate the relationship. Age differences give different results towards kindergarten teachers' subjective well-being. The theoretical and practical implications of these findings are discussed in the discussion. Subjective well-being pada guru taman kanak-kanak dianggap penting untuk keberhasilan dalam proses belajar mengajar. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh kebersyukuran terhadap subjective well-being pada guru TK yang dimoderatori oleh usia. Metode penelitian yang digunakan menggunakan pendekatan kuantitatif, dengan jumlah responden 72 guru TK Aisyiyah di Purwokerto. Instrumen yangdigunakan adalah skala subjective well-being yang dimodifikasi dari skalaSWLS dan SPANE milik Diener et al (2009) dengan Cronbach ⍺ = 0,839 (15 aitem), skala kebersyukuran dimodifikasi dari skala GRAT milik Watkins, Woodward, Stone, dan Kolts (2003) dengan Cronbach ⍺ = 0,901 (32 aitem), serta data demografi usia. Teknik analisis data yang digunakan yaitu regresi berganda untuk mengetahui pengaruh variabel dan efek moderasinya, dibantu dengan software Jamovi 1.8.4. Hasil analisis menunjukkan bahwa terdapat pengaruh signifikan kebersyukuran terhadap subjective well-being pada guru TK. Usia juga terbukti secara statistik dan signifikan dapat memoderasi hubungan tersebut. Adanya perbedaan usia, memberikan hasil yang berbedapula pengaruhnya terhadap subjective well-being guru. Implikasi teoritis dan praktis dari temuan ini dibahas dalam diskusi.